A demographic model to support an impact financing mechanism for black rhino metapopulations. (May 2021) - Barichievy, Chris; Altwegg, Res; Balfour, Dave; Brett, Rob; Gordon, Chris; Henry, Dominic A.W.; Jeffries, Glen; Khayale, Cedric; Wanyama, Horris; Withers, Oliver
Abstract: Payment-for-results mechanisms have the potential to increase funding for Critically Endangered species such as the black rhino ( Diceros bicornis ). Developing such financial mechanisms requires an understanding of the efficacy of conservation interventions, the potential conservation return on investment and an ability to rigorously measure the impact of interventions, such as change in abundance of live or poached animals. However, imperfect detection must be considered to derive robust estimates of these measures. Managing black rhino is often done at the metapopulation level (in distinct management units) where ecological and observational processes can differ substantially between populations. We developed a multi-state capture-mark-resight model to estimate the abundance of live rhino and carcasses from annual historical observations. We used age, sex and management units as covariates. We used 25 years of monitoring data from two sections with contrasting rhino densities in Tsavo West National Park, Kenya as a test case. The model presented can be used to estimate abundances of rhino from historical data and provides a mechanism to measure changes across multiple management sections. We foresee this model being used as the basis for impact measurement of a rhino impact financing mechanism. The model can easily be modified for use in other species managed in a metapopulation framework.